Effect of butt joint on mechanical properties of welded low carbon steel - Wardoyo, T.; Izman, S.; Kurniawan, Denni (2014)
Effect of variation of the connection (butt joint) in low carbon steel resistance welding (shielded metal arc welding, SMAW) performance is investigated in this paper. Three types of butt joint was varied: square, single V, and double V. The results from tensile test showed that welded specimens are of similar tensile properties with base metal and one another. When hardness test was performed on weld metal, HAZ, and base metal of each specimen,.it was found that weld metal and HAZ were of higher hardness than the base metal. Specimen with square joint exhibits the highest hardness while specimens with single V and double V joints show similar hardness. Microstructure analysis revealed that weld metal of specimen with square joint is of bainite-martensite phases while weld metal of specimens with single V and double V joints are of ferrite-pearlite phases. This difference in microstructure, and hence in hardness, is related to the corresponding heat input during welding. © (2014) Trans Tech Publications, Switzerland.